Fiscal sustainability and the fiscal reaction function for South Africa - Jooste, Charl (IMF Working Papers; Working Paper ;, 2011)
How does the South African government react to changes in its debt position? In investigating the question, this paper estimates fiscal reaction functions using various methods (OLS, VAR, TAR, GMM, State-Space modelling and VECM). The paper finds that since 1946 the South African government has ran a sustainable fiscal policy, by reducing the primary deficit or increasing the surplus in response to rising debt. Looking ahead, the paper considers the use of fiscal reaction functions to forecast the debt/GDP ratio and gauging the likelihood of achieving policy goals with the aid of probabilistic simulations and fan charts.